Bez obrazu, czyli seriale audio. Problematyka kreacji świata przedstawionego i jego recepcji - Agnieszka Ogonowska (Studia Filmoznawcze)
The aim of the article is to show the issues related to the world-building present in audio series in relation to various types of acoustic spaces, a bank of sounds specific to real spaces and the creation of shared fields of action and relations within a given universe in the mind of the recipient. Further attention is paid to the issue of differentiating individual characters by creating distinctive language and sound profiles that mark them out as individuals, as well as assigning them specific sound attributes related to verbal and non-verbal communication and the soundscape characteristic of a specific place of action or social environment. The analysis also takes into account the role of diegetic and non-diegetic sounds in creating the imaginary world and controlling the recipient’s expectations, as well as the processes of understanding and interpreting (or analyzing) the audio series. The article also draws attention to the role of silence, (un)silence and various types of pauses as meaningful aspects of communication and interactions between the characters of the audio series. A separate section is devoted to the characteristics of the elements of the imaginary audio space in the context of individual cognitive universals. The conceptual framework for the analysis of these issues will be intermediality treated as (a) a process of adaptation, but also, in “adjectival” form, as (b) a specific attribute of an audio-series, i.e. an intermedia message and as (c) a user competency attribute. The article is not normative, but descriptive, i.e. it describes creative and reception practices related to the eponymous phenomenon. Due to the breadth of the research field, two perspectives are used in the article: the medium-oriented approach and the user-oriented approach.